2005
DOI: 10.1093/bja/aei099
|View full text |Cite
|
Sign up to set email alerts
|

Laryngospasm during subarachnoid block

Abstract: Central neuraxial block is associated with increased vagal tone. We report a patient who developed laryngospasm and stridor under spinal anaesthesia. This was treated successfully with i.v. atropine and fluids. We propose that the laryngospasm was secondary to increased vagal tone under the spinal anaesthetic. Such a manifestation of increased vagal tone under spinal anaesthesia has not been reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Editor-We congratulate Visser and colleagues on applying glucose-insulin-potassium (GIK) therapy using a hyperinsulinaemic normoglycaemic clamp. 1 Their study confirms our findings that the clamp technique is an effective, and to date the only, method of maintaining normoglycaemia in patients undergoing coronary artery bypass grafting surgery. 2 In addition, they demonstrated, for the first time in this population, the attenuation of systemic inflammation with perioperative GIK therapy.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Editor-We congratulate Visser and colleagues on applying glucose-insulin-potassium (GIK) therapy using a hyperinsulinaemic normoglycaemic clamp. 1 Their study confirms our findings that the clamp technique is an effective, and to date the only, method of maintaining normoglycaemia in patients undergoing coronary artery bypass grafting surgery. 2 In addition, they demonstrated, for the first time in this population, the attenuation of systemic inflammation with perioperative GIK therapy.…”
supporting
confidence: 82%
“…Editor-We thank Drs Carvalho, Leung and Schricker for their comment on our study. 1 It is true that we did not succeed in preventing hypoglycemia, (blood glucose <3 mmol litre À1 ) in all our patients at all times. Glucose levels between 2.2 and 3.0 mmol litre À1 were found in 7 out of 175 blood samples (4%) obtained during the first 5 h of the study.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…However, it could be suggested that the apnea was caused by a tonic contraction of the upper airway, which is known to cause obstructive apnea [ 24 ]. It has been proposed that ictal laryngospasm could be driven by tonic seizure discharge spread to cortical areas governing laryngeal motor control (perisylvian motor cortex and anterior insula) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia occurred in 25 (75%-89%). The severity of hypoxemia was significantly associated with apnea duration (R = −0.620, p < 0.001; Figure 3).…”
Section: Ictal Hypoxemiamentioning
confidence: 99%